2013
DOI: 10.1096/fj.12-219964
|View full text |Cite
|
Sign up to set email alerts
|

Production, characterization, and antigen specificity of recombinant 62‐71‐3, a candidate monoclonal antibody for rabies prophylaxis in humans

Abstract: Rabies kills many people throughout the developing world every year. The murine monoclonal antibody (mAb) 62-71-3 was recently identified for its potential application in rabies postexposure prophylaxis (PEP). The purpose here was to establish a plant-based production system for a chimeric mouse-human version of mAb 62-71-3, to characterize the recombinant antibody and investigate at a molecular level its interaction with rabies virus glycoprotein. Chimeric 62-71-3 was successfully expressed in Nicotiana benth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…Expression levels of up to 3-4 % TSP (*100 mg/kg fresh tissue weight) were achieved, which were sufficient to purify and characterize the plant-made antibody. In terms of functionality, the plant-made mAb 62-71-3 bound to its antigen and neutralized a rabies pseudotype virus [58]. An important conclusion of this research is the strong neutralizing activity in the FAVN assay (500 IU/mg), which is similar to that of the murine hybridoma-derived counterpart [59].…”
Section: Plant-made Anti-rabies Virus Antibodiesmentioning
confidence: 68%
See 1 more Smart Citation
“…Expression levels of up to 3-4 % TSP (*100 mg/kg fresh tissue weight) were achieved, which were sufficient to purify and characterize the plant-made antibody. In terms of functionality, the plant-made mAb 62-71-3 bound to its antigen and neutralized a rabies pseudotype virus [58]. An important conclusion of this research is the strong neutralizing activity in the FAVN assay (500 IU/mg), which is similar to that of the murine hybridoma-derived counterpart [59].…”
Section: Plant-made Anti-rabies Virus Antibodiesmentioning
confidence: 68%
“…A pioneering study conducted by McGarvey et al [35] demonstrated that the G protein can be expressed in tomato Neutralized a rabies pseudotype virus [58,59] plants using a standard nuclear expression approach driven by the 35SCaMV promoter and an Agrobacterium-mediated transformation procedure. Although yields were very low, 1-10 ng/mg soluble protein, the proof of the concept opened important prospects to continue research in this area.…”
Section: Plant-based Vaccine Prototypes Against Rabies G Protein Prodmentioning
confidence: 99%
“…This is particularly important as several virus-neutralizing monoclonal antibodies (MAbs) were offered for replacement of conventional HRIG in human rabies PEP (21)(22)(23)(24)(25)(26)(27)(28). For example, a linear epitope with the key residues LCGV within antigenic site I serves for binding of MAbs CR57 and 62071-3 (22,23). Similarly, conserved conformational antigenic sites II and III contain binding epitopes for several other MAbs (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…96 Homologous products (recombinant) -fully human intact igG Important parameters that drive selection of the most optimal systems for expression of antibodies include basic structure, protein folding and glycosylation, 97 productivity, ease of purification, 98 product quality and quantity, safety issues, time to clinic and market, and economic considerations such as cost of goods and regulatory issues. 99 In general, eukaryotic systems such as mammalian cells, 99,100 insect cells, 97 yeast, 101 plants, 74,102 green algae, 103 and transgenic animals 104 hold the greatest promise for expressing recombinant human MAbs. However, mammalian cells are predominantly used because they can correctly fold, assemble, glycosylate, and secrete antibodies.…”
Section: Native -Human Mabs -Full Lengthmentioning
confidence: 99%
“…MAb 62-71-3 was expressed in tobacco leaves and found to be an appropriate candidate MAb in the making of a novel antibody cocktail 74. …”
mentioning
confidence: 99%